2019
DOI: 10.1002/adbi.201900023
|View full text |Cite
|
Sign up to set email alerts
|

Printing Life‐Inspired Subcellular Scale Compartments with Autonomous Molecularly Crowded Confinement

Abstract: A simple, rapid, and highly controlled platform to prepare life‐inspired subcellular scale compartments by inkjet printing has been developed. These compartments consist of fL‐scale aqueous droplets (few µm in diameter) incorporating biologically relevant molecular entities with programmed composition and concentration. These droplets are ink‐jetted in nL mineral oil drop arrays allowing for lab‐on‐chip studies by fluorescence microscopy and fluorescence life time imaging. Once formed, fL‐droplets are stable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 63 publications
(91 reference statements)
1
21
0
Order By: Relevance
“…[31,33] Differently from previously developed set-ups such as satellites printing or droplet generation in liquid environments [82,83] which have not been demonstrated to be suitable for biomolecular systems, our group has recently designed a printing approach based on piezoelectric IJP for the fabrication of artificial compartments at fL scale. [85] In particular, by following the theoretical model from Eggers and coworkers, [195] in which the droplet size can be finely tuned by minimizing the actuation time of the transducer, we were able to produce Figure 7C). In turn, the downscaling at the fL-size triggered the formation of molecularly crowded shells at the water/oil interface, with a typical thickness in the order of hundreds of nanometers, in accordance with models.…”
Section: Printing Protein-rich Aqueous Liquid Microcompartmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31,33] Differently from previously developed set-ups such as satellites printing or droplet generation in liquid environments [82,83] which have not been demonstrated to be suitable for biomolecular systems, our group has recently designed a printing approach based on piezoelectric IJP for the fabrication of artificial compartments at fL scale. [85] In particular, by following the theoretical model from Eggers and coworkers, [195] in which the droplet size can be finely tuned by minimizing the actuation time of the transducer, we were able to produce Figure 7C). In turn, the downscaling at the fL-size triggered the formation of molecularly crowded shells at the water/oil interface, with a typical thickness in the order of hundreds of nanometers, in accordance with models.…”
Section: Printing Protein-rich Aqueous Liquid Microcompartmentsmentioning
confidence: 99%
“…Note that several reports have demonstrated the possibility to tune droplet formation dynamics by using a set of different boundary conditions that involve hydrodynamic droplet dispensing under electrical field guiding, [81] droplets production within liquid environments, [82] satellite droplets printing, [83] breaking up in a double-orifice system, [84] reducing the impulse duration time. [85] Other approaches that can reach sub-cellular scale resolution include electrohydrodynamic, [70] or pyroelectrodynamic dispensing. [71] One hurdle of these approaches is that they are associated with significant shear/compression stresses that can ultimately lead to the alteration of the biomolecular structures and functions.…”
Section: Droplet Formation: Defining the Operative Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it is possible to integrate the hardware with automated translation stages, allowing precise pattern placement and registration to prepare multilayered patterns with different materials. Inkjet printing has found many applications in the field of direct patterning of many different materials, such as colloidal silver nanoparticles [58], oil droplets [8], biomolecular systems [59][60][61]. Notably, the rheological properties of the ink play a fundamental role in the printing process.…”
Section: Inkjet Printingmentioning
confidence: 99%
“…Notably, the droplet diameter is usually similar or slightly larger than the size of the nozzle. However, some reports have shown that it is possible to reduce its size by adapting waveform [61] or by employing satellite printing [63].…”
Section: Inkjet Printingmentioning
confidence: 99%